(untitled) (ModaPalavra e-periódico, 2025)
This article deals with a trend within sustainable fashion, which is the creation and production of inclusive clothing for different physical types and agender, in order to break down barriers and make fashion accessible to everyone. In this way, it aims to map inclusive fashion strategies present in brands in the clothing industry in the city of Curitiba/PR focused on sustainability. This approach is part of a doctoral research on guidelines for the future of sustainable fashion work. The methodology includes, in addition to the literature review, the collection of data on the brands in question, obtained in interviews, on the internet and in a workshop aimed at capturing the vision of experts on the subject. The descriptive and qualitative analyses confirm important points of inclusive fashion for sustainability, such as the availability of pieces that dress the plurality of people, with good modeling and that provide the feeling that one is not on the margins of fashion.